Multidrug Resistance and Invasive Medical Device Use with Staphylococcus aureus Biofilm Formation in Riau - Mansyar, Putri Purnama Sari; Nuryastuti, Titik; Anggraini, Dewi (Sarana Ilmu Indonesia (Salnesia), 2025)
Staphylococcus aureus (S. aureus) infection is a major cause of healthcare-associated infections, particularly among patients using invasive medical devices. These devices provide surfaces for bacterial adhesion and biofilm formation, a key mechanism that enhances antibiotic resistance, especially in multidrug-resistant (MDR) strains. This study aimed to analyze the association between MDR status and invasive medical device use with biofilm formation in clinical isolates of S. aureus at Arifin Achmad General Hospital, Riau Province. This was an analytic-observational study with a cross-sectional design involving 44 clinical isolates of S. aureus collected from patients between January and April 2025. Biofilm formation was assessed using the Microtiter Plate Assay (MtPA), and antibiotic susceptibility testing was conducted using the Vitek 2 System. Demographic and clinical data of the subjects, such as gender, age, and use of invasive medical devices, were obtained from medical records. The relationship was analyzed using the Chi-square test. The results showed that out of 44 clinical isolates of S. aureus, 29 isolates (65,91%) were capable of forming biofilm. There was a significant association between MDR status (p-value = 0,026) and the use of invasive medical devices (p-value = 0,019) with biofilm formation (p-value < 0,05). These findings indicate that MDR status and the use of invasive medical devices may contribute to the increased ability of S. aureus clinical isolates to form biofilms. Therefore, strengthening infection control measures and rationalizing the use of invasive medical devices are essential to prevent persistent infections that are difficult to treat due to biofilm formation.